2007
DOI: 10.1111/j.1462-2920.2007.01418.x
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid adhesins are abundant in natural biofilms

Abstract: Surface-associated amyloid fibrils have been described by bacteria in the family Enterbacteriaceae, but it is unknown to what extent amyloid adhesins are present in natural biofilms. In this study, amyloid adhesins were specifically stained with Thioflavin T and two conformationally specific antibodies targeting amyloid fibrils. These three independent detection methods were each combined with fluorescence in situ hybridization using fluorescently labelled oligonucleotide probes in order to link phenotype with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
244
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 281 publications
(252 citation statements)
references
References 73 publications
6
244
1
1
Order By: Relevance
“…Generally, the function of amyloid fibrils is assumed to be related to enhanced adhesion to surfaces (49) and biofilm formation, but they may also increase resistance to chlorine (55) and resistance to chemical and enzymatic digestion (45). The function in activated sludge flocs is still unknown but may be related to the aggregation of microorganisms internally in microcolonies, whereas it is more uncertain what the function is in the filamentous bacteria, which were also shown to produce amyloids (32). Activated sludge flocs are often described as having a strongly and loosely bound fraction of cells and EPS (23,57), so amyloids might be a good candidate for contributing to the high stability of the strongly bound fraction.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Generally, the function of amyloid fibrils is assumed to be related to enhanced adhesion to surfaces (49) and biofilm formation, but they may also increase resistance to chlorine (55) and resistance to chemical and enzymatic digestion (45). The function in activated sludge flocs is still unknown but may be related to the aggregation of microorganisms internally in microcolonies, whereas it is more uncertain what the function is in the filamentous bacteria, which were also shown to produce amyloids (32). Activated sludge flocs are often described as having a strongly and loosely bound fraction of cells and EPS (23,57), so amyloids might be a good candidate for contributing to the high stability of the strongly bound fraction.…”
mentioning
confidence: 99%
“…Recently, we found that proteinaceous amyloid adhesins are an abundant component of the EPS fraction in biofilms from different habitats among these activated sludge flocs (32). Bacterial amyloids are usually thin fibrils, insoluble, and extremely resistant to various denaturants (8).…”
mentioning
confidence: 99%
See 3 more Smart Citations